The Effect of Flash Animation-Based Discovery Learning on Students’ Chemical Bonding Learning Outcomes - Nur Hikma; Ramdani Ramdani; Eda Lolo Allo (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2026)
This study aims to determine the effect of Macromedia Flash-based animation media within the Discovery Learning model on the learning outcomes of Grade XI MIPA students at MA Manongkoki, Takalar Regency, in the subject of Chemical Bonding. The research used a quasi-experimental design with a quantitative approach and employed a posttest-only control group design. The sampling technique was random sampling. The study population consisted of all three Grade XI MIPA classes, with XI MIPA 1 as the experimental group and XI MIPA 2 as the control group. A multiple-choice test was used as the research instrument to collect data on student learning outcomes. Data analysis was conducted using descriptive and inferential statistics. The descriptive results showed that the experimental class achieved a higher average score (83.92) than the control class (71.08). Inferential statistical analysis indicated that the data were not normally distributed; therefore, the Mann-Whitney test was used. The analysis yielded a Zcount value of 3.11, which was greater than the Ztable value of 1.65. Based on these results, it can be concluded that Macromedia Flash-based animation media within the discovery learning model has a significant positive effect on students’ learning outcomes in chemical bonding.